Whole Genome Sequencing Reveals Major Deletions in the Genome of M7, a Gamma Ray-Induced Mutant of Trichoderma virens That Is Repressed in Conidiation, Secondary Metabolism, and Mycoparasitism - Pachauri, Shikha; Sherkhane, Pramod D.; Kumar, Vinay; Mukherjee, Prasun K. (Frontiers in Microbiology, 2020)
Trichoderma virens is a commercial biofungicide used in agriculture. We have earlier isolated a mutant of T. virens using gamma-ray induced mutagenesis. This mutant, designated as M7, is defective in morphogenesis, secondary metabolism and mycoparasitism. The mutant does not produce conidia and the colony is hydrophilic. M7 cannot utilize cellulose and chitin as sole carbon source, and is unable to parasitize the plant pathogens Rhizoctonia solani and Pythium aphanidermatum in confrontation assay. Several volatile (like germacrenes, beta-caryophyllene, alloaromadendrene, gamma-muurolene) and non-volatile (viridin, viridiol, gliovirin, heptelidic acid) metabolites are not detected in M7. In transcriptome analysis, many genes related to secondary metabolism, carbohydrate metabolism, hydrophobicity and transportation, among others, were found to be down-regulated in the mutant. Using whole genome sequencing, we identified five deletions in the mutant genome, totaling about 250 kb (encompassing 72 predicted ORFs), which was confirmed by PCR. This study provides novel insight into genetics of morphogenesis, secondary metabolism and mycoparasitism, and eventually could lead to the identification of novel regulators of beneficial traits in plant beneficial fungi Trichoderma spp. We also suggest that this mutant can be developed as a microbial cell factory for the production of secondary metabolites and proteins.